Analysis Of Business Feasibility In Terms Of Market And Marketing Aspects Of The Aman Sasirangan Business - Nurhafiyanisa, Nurhafiyanisa (Robust: Research of Business and Economics Studies, 2024)
Each tribe has various unique characteristics and customs, such as variations on themes, costumes, and traditional handwork. For example, one of the very unique and unusual arts in South Kalimantan is sasirangan fabric. One example of this is the Aman Sasirangan business, which produces sasirangan fabrics. The purpose of this study is to understand and see whether the Aman Sasirangan business deserves to be said to be an udaha, in terms of market and marketing aspects. One type of research conducted is descriptive research. Data analysis techniques include market and marketing analysis. The subject matter of this research can include market and marketing analysis. The research findings show that Aman Sasirangan can be predicted to be viable when a thorough analysis of the business research is conducted. This is related to market and sales trends that include product development, sales growth in the surrounding area, promotional activities and price phase adjustments such as the use of creative advertising, social media, and cooperation with local communities, which can have a positive impact on business potential.